2023
DOI: 10.1111/apt.17525
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of switching from adalimumab originator to adalimumab biosimilar in patients with inflammatory bowel disease: The ADA‐SWITCH study

Abstract: Summary Background and Aims Data on the outcomes after switching from adalimumab (ADA) originator to ADA biosimilar are limited. The aim was to compare the treatment persistence, clinical efficacy, and safety outcomes in inflammatory bowel disease patients who maintained ADA originator vs. those who switched to ADA biosimilar. Methods Patients receiving ADA originator who were in clinical remission at standard dose of ADA originator were included. Patients who maintained ADA originator formed the non‐switch co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Despite an initial reticence to use biosimilars, these compounds have gained prominence, and mounting evidence supports their use in clinical practice, as well as the switch to their use in patients who start on the original drug [33,34]. Moreover, their introduction in IBD treatment is expected to reduce the economic burden on healthcare systems [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite an initial reticence to use biosimilars, these compounds have gained prominence, and mounting evidence supports their use in clinical practice, as well as the switch to their use in patients who start on the original drug [33,34]. Moreover, their introduction in IBD treatment is expected to reduce the economic burden on healthcare systems [35].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few real-life studies have investigated the switch to adalimumab biosimilars [11][12][13][14][15][16][17][18][19][20], and a majority of these studies have not included a comparison group of patients receiving the original treatment. The present study was aimed to address this research gap by comparing the time of persistence between adalimumab biosimilars and the reference drug in a cohort of patients, including a mixed group that made the switch from the originator to the biosimilar.…”
Section: Introductionmentioning
confidence: 99%
“…4 In previous real-world comparative studies, no significant differences in drug retention, effectiveness and safety were found between biosimilars and Humira for inflammatory bowel diseases and rheumatic diseases. [5][6][7][8] However, studies investigating hidradenitis suppurativa treatment have suggested that switching from the originator to biosimilars was associated with increased risks of ineffectiveness and treatment discontinuation. 9 10 For the treatment of psoriasis, evidence is predominantly derived from short clinical trials, with only one small real-world study comparing biosimilars to Humira.…”
Section: Introductionmentioning
confidence: 99%